Effect of lockdown on routine immunization services in a tertiary care hospital of Rajasthan, India: quarterly analysis - Dhamania, Madhvi; Akhter, Javed; Rathore, Sunil Singh; Gaur, Kusum (International Journal of Contemporary Pediatrics, 2023)
Background: Lockdown was used as a tool to control COVID-19 but it has resulted in the disruption of routine immunization services both in India and globally. Present study aimed to estimate the effect of COVID-19 lockdown periods during years 2020 and 2021 on routine immunization at tertiary-care hospital in Jaipur, Rajasthan, India. Methods: A retrospective record-based observational study was conducted at paediatric tertiary-care hospital, Jaipur. Data were collected from the immunization records of the centre for the vaccines administered to children (0-16 years) under the universal immunization programme (UIP) from January 2019 to December 2021. Doses administered were assessed as a proxy measure of vaccine coverage. The vaccination trends were compared with base year 2019. unpaired ‘t’ test of significance and percent change were used for statistical analysis. Results: The effect of lockdown was maximum in the second quarter of both years 2020 and 2021 with the declination of the total vaccine doses administered by -49.9% and -36.2% respectively. The first lockdown period in year 2020 recorded maximum negative difference in dose of Td (10 years) (-98.4%) followed by DPT booster-2 (-83.6%). The second lockdown in year 2021 recorded maximum negative difference in dose of Td (16 years) (-62.5%) followed by Td-10 years (-58.1%) and DPT booster-2 (-56.5%). Conclusions: This study concludes that the least vaccine doses were administered in second quarter of both years which coincides with lockdown period. Hence during emergencies like lockdown other alternative arrangement for continuance of routine immunization may be implemented.